Empowering Students’ Speaking Ability by Technology Utilization - Veni Nella Syahputri; Lilik Yulianingsih (Seumike : Society Progress Journal, 2025)
The increasing importance of English communication in today’s globalized world necessitates effective language learning strategies, especially in speaking. However, traditional teaching methods often fail to engage students and build their confidence in speaking. This study explores the role of technology in improving students' speaking skills in English language learning, focusing on tools such as speech recognition software, language exchange platforms, and interactive video conferencing. Using a mixed-methods approach, the study involved 120 undergraduate students in a quasi- experimental design with a control and an experimental group. The experimental group utilized digital tools for speaking practice, while the control group received traditional instruction. The results indicated significant improvements in fluency, pronunciation, and overall speaking confidence in the experimental group. Survey and observational data also showed higher levels of student engagement and motivation. The study concludes that integrating technology into English language teaching can effectively enhance speaking skills by providing immersive, interactive learning experiences that foster autonomy and confidence. These findings highlight the potential of technology to bridge gaps in traditional language learning approaches.